PENGARUH CURRENT RATIO (CR), CASH RATIO, DEBT TO EQUITY RATIO (DER), DAN RETURN ON INVESTMENT (ROI)TERHADAP DIVIDEND PER SHARE (STUDI PADA PERUSAHAAN PROPERTY DAN REAL ESTATE YANG TERCATAT DI BEI) - Ahmad Shodikin (Manajemen Bisnis, 2014)
The study aims to examine the effect of Current Ratio (CR), Cash Ratio, Debt to Equity Ratio (DER), Return on Investment (ROI) on Dividend Per Share (Study at Property and Real Estate Company listed in BEI). Multiple regression analysis used to analyze data. Secondary data was taken from 68 respondents in the BEI (Indonesian Capital Market Directory, KSEI, and www.idx.co.id) and the oobservation period from 2009 to 2012. The result indicated that current ratio, cash ratio, debt to equity ratio, and return on investment have simultaneously efect on dividend per share. Partially, Current Ratio, Cash Ratio, Return on Investment have a negative effect on Dividend Per Share. While Debt to Equity Ratio has no effect to Dividend Per Share. Return on Investment has a dominant effect on Dividend Per Share. Keywords: Current Ratio (CR), Cash Ratio, Debt to Equity Ratio (DER), Return On Investment (ROI), Dividend Per Share (DPS)